Pengaruh Good Corporate Governance, Profitabilitas dan Kebijakan Dividen terhadap Nilai Perusahaan - Silvia Thauziad; Masiyah Kholmi (JURNAL MUTIARA AKUNTANSI, 2021)
The aim of this study is to test empirically the effect of managerial ownership, institutional ownership, profitability, and dividend policy on firm value. The population in this study are all companies listed on the Indonesia Stock Exchange in the 2017-2019 period. The sampling technique used in this study was a purposive sampling method. The sample obtained was 105 companies with 3 years of observation. The data analysis model in this study is panel data regression using EViews10 software. The result of the research shows that managerial ownership, institutional ownership, profitability and dividend policy have a significant influence to firm value. Meanwhile, managerial ownership,institutional ownership, profitability have asifnificant influence to firm valye partially. But dividend policy have no significant influence to firm value partially.